Women’s attitude towards breast cancer in Baghdad city, Iraq - Hasan, Tiba Nezar; Shah, Shamsul Azhar; Ghazi, Hasanain Faisal; Hassan, Mohd Rohaizat (International Journal Of Community Medicine And Public Health, 2017)
Background: Breast cancer is the most common cancer among women all over the world. The aim of this study was to measure the attitude of women regarding breast cancer and its associated factors in Baghdad city, Iraq. Methods: A cross-sectional study was done among 508 women aged 18 years old and above recruited randomly from 4 Non-Governmental Organizations (NGO) in Baghdad City during 2015. A self-administered questionnaire was used to collect the data from respondents. Results: A total of 66.1% had a good attitude, the association between attitude and marital status, education was not significant, while working status was significant with P value of 0.001. After controlling for other cofounders, the contributors for poor attitude were not working, P value of 0.002 and adjusted odds ratio of 2.08. Conclusions: The attitude among the respondents still considered not good as almost one-thirds of the respondents had poor attitude. The most important contributor to poor attitude was working status. More education and health promotions need to be done among general population to educate them regarding breast cancer in Baghdad City, Iraq.